Analisis Penerapan Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM (Studi Kasus pada UMKM CV. NELL’Q PERSADA MANDIRI) - Sulistia Suwondo (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
Financial statements are reports that show conditions and provide financial information at present or in a certain period. This study aims to facilitate MSMEs in preparing financial reports in accordance with SAK EMKM. The purpose of this study was to determine how the preparation of financial statements that have been made by CV. NELL'Q PERSADA MANDIRI and what obstacles are faced in preparing financial reports based on SAK EMKM. This research uses a qualitative descriptive approach with a case study method. for data collection is done by observation, interviews, and documentation. The results of this study indicate that the preparation of financial reports has not fully implemented SAK EMKM, this is due to the limited understanding of MSMEs related to SAK EMKM.